Retrospective Analysis of Work From Home for Civil Servants During The Covid- 19 Pandemic - Gugun Geusan Akbar; Nita Nurliawati; Muchtar Muchtar; Abdullah Ramdhani (Jurnal Borneo Administrator, 2021)
The COVID-19 pandemic hitting Indonesia has created new habitual adaptations, including working from home for civil servants. This policy presents a new challenge, namely maintaining performance through achieving the effectiveness of working from home. The present study investigates the implementation of the work from home policy through Spearman's rank-order correlation analysis to examine the correlation between research variables. Furthermore, after the Kruskal-Wallis significant test, the Dunn-Bonferroni post hoc method was used to look for the differences between the factors affecting the effectiveness of working from home of the civil servants based on gender and age and education, and years of service. Data were collected through questionnaires to 437 civil servants from various government agencies, both central and regional. The study's findings indicate differences in the factors influencing the effectiveness of working from home and the skills required depending on gender, age, education, and years of service. The results also show that information technology support is not evenly distributed in implementing the work from home policy. The implication of this study suggests that the evaluation of the implementation of the work from home policy for the civil servants is beneficial for the government in considering sustainability and quality development in the future.